Price Determinants of Scholarly Business Books: An Econometric Model. Issue 3 (1st October 2017) - Terng, Charles
Abstract: This study examines important factors affecting the price of scholarly books in the business disciplines. The data consist of over 2800 titles in areas of Accounting, Economics, Finance, Management, and Marketing. Using an econometric model, the impact of commercial publishers, the e-book market, and several product and publisher attributes were shown to have significant influence on pricing. Implications of this study can further inform economical purchasing decisions and policy-making with the support of empirical evidence.